2001
DOI: 10.1039/b103052n
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The synthesis of 13 discotic mesogens is described in which the well-known hexakis(pentyloxy)triphenylene liquid crystalline material has been chemically modified to incorporate one, two, three and six carbazole moieties. These modifications have been achieved by the alkylation or esterification of mono-, di-, tri-and hexa-hydroxytriphenylene derivatives with alkyl bromides and carboxylic acids incorporating the carbazole moiety. The pure compounds are not liquid crystalline in nature but when doped with TNF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…It was shown that the resulting molecules did not possess liquid-crystalline behavior but could form hexagonal columnar mesophases of various stability, induced by TNF doping. 519 However, this occurred only when the carbazole substitution did not exceed two, indicating that the higher substituted compounds do not display ordered stacking behavior.…”
Section: Covalent Donor−acceptor Liquid Crystalsmentioning
confidence: 98%
“…It was shown that the resulting molecules did not possess liquid-crystalline behavior but could form hexagonal columnar mesophases of various stability, induced by TNF doping. 519 However, this occurred only when the carbazole substitution did not exceed two, indicating that the higher substituted compounds do not display ordered stacking behavior.…”
Section: Covalent Donor−acceptor Liquid Crystalsmentioning
confidence: 98%
“…It was reported that the 1∶1 mixture of electron-rich and electron-poor discogens displayed wider mesophase ranges and higher ordered columnar mesophases than the components. [24][25][26][27][28] Figure 2 showed POM texture photographs of columnar mesophases of the prepared triphenylene discogens. Those are typical fan-shaped textures of columnar mesophases.…”
Section: Resultsmentioning
confidence: 99%
“…In triphenylene based material design, peripheral sulfur atom promoted molecular self assembly, 11 hydrophilic and hydrophobic effect, 12 fluorophilic effect of perfluoroalkyl chain, [13][14][15] hydrogen bonding, 16 asymmetrical substitution, [17][18][19][20][21][22][23] electronic donor acceptor interaction, 24,25 complimentary polytopic interaction, 26,27 and arene perfluoroarene interaction 28 have been exploited for improving mesophase range, order of mesophase, and alignment behavior of discogens.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,7,10,11-pentahexyloxy-2-hydroxy-triphenylene 1 was prepared according to literature [9]. 2 is easily obtained by reacting 1 with excess amount of 3-bromopropanol.…”
Section: Methodsmentioning
confidence: 99%